2018
DOI: 10.1097/sle.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pulmonary Complications After Laparoscopic Pylorus-preserving Pancreaticoduodenectomy: A Retrospective Observational Analysis

Abstract: Laparoscopic pylorus-preserving pancreaticoduodenectomy (LPPPD) is less invasive than open pylorus-preserving pancreaticoduodenectomy. However, LPPPD has a long operation time with pneumoperitoneum, which may affect the postoperative pulmonary complications (PPCs). We retrospectively evaluated the incidence of PPCs and their risk factors in LPPPD. In 191 patients who underwent LPPPD, the incidence of PPCs was 28.8% (n=55). Multivariate logistic regression analysis revealed that the risk factors for PPCs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In agreement with previous results [5,37,50], the present study also found that the rate of ICU admission and the length of ICU stay were significantly greater in prostate cancer patients with than without PPCs [5,37,50]. PPCs are associated with increases in morbidity, including acute renal failure and myocardial infarction, as well as increases in mortality rates and hospital costs [6,51].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous results [5,37,50], the present study also found that the rate of ICU admission and the length of ICU stay were significantly greater in prostate cancer patients with than without PPCs [5,37,50]. PPCs are associated with increases in morbidity, including acute renal failure and myocardial infarction, as well as increases in mortality rates and hospital costs [6,51].…”
Section: Discussionsupporting
confidence: 92%
“…Albumin, a biomarker for nutrition state, was shown to be related to postoperative complications, such as surgical site infection, and to postoperative outcomes [35,36]. Hypoalbuminemia has been significantly associated with poor postoperative outcomes, especially PPCs [37,38]. Several hypotheses have suggested the mechanisms by which hypoalbuminemia is associated with the development of PPCs [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous studies demonstrated that male sex, older age, and high body mass index were independent risk factors of PPCs in robot-assisted laparoscopic prostatectomy, percutaneous nephrolithotomy, and laparoscopic pylorus-preserving pancreaticoduodenectomy. 7 , 8 , 56 These differences in independent risk factors for PPCs may be, at least in part, explained by differences in the patient characteristics and the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…postoperative morbidity and mortality associated with cardiopulmonary and renal complications are of major concern in patients undergoing surgery (2)(3)(4)(5)(6). Early identification and management of postoperative complications are essential during the perioperative period (7)(8)(9)(10)(11). This Research Topic of Frontiers in Medicine introduces interesting studies for the new evaluation and management for improvement in postoperative morbidity and mortality.…”
mentioning
confidence: 99%